Projections in the national mining development plan (nmdp) using @risk (2014)
The mining industry in Colombia has reached an important position in the international market and the national economy, so, in order to describe the dynamics of the mining market, analyze the structure of the industry and make a comparison with estimates mineral production released at the National Mining Development Plan (PNDM) Unidad de Planeacion Minero Energetica (UPME), the @Risk tool is implemented. This tool and methodology defined in this article, allows for uncertainty and risk estimates in a simulation that generates a projection with a time horizon to 2019 the historical mining (extraction considering among years 1970 to 2013) of coal, gold and limestone, building alternative models that can be replicated by the mining institution in their respective futures PNDM and its updates.